Burying the Kasuku Syndrome: Constructing Inventive Sites of Knowledge - Gĩthae Mũgo, Mĩcere (Strathmore Law Journal, 2021)
Having come here to advocate the immediate burial of ‘kasuku culture,’ alias, ‘parrot culture,’ I had better initiate the process of grave-digging myself. As an African academician, poet, playwright, artist, cultural worker and activist, I have sought to do this in different ways. One such way has been using my intellectual work to affirm progressive indigenous African paradigms, including orature, which Pio Zirimu and Austin Bukenya once concisely defined as ‘verbal art.’1 I will, therefore, use an African Orature style of delivery to hold this conversation with you. I cannot think of a more appropriate tool of competing with fatigue at the end of a long day, or of keeping a possible dozing audience alive, following such a challenging dinner. My talk, or palaver, will be divided into movements or cycles, labelled palaver one to ten. Inside each of these full stream palavers will be meandering tributaries of smaller, but related palavers. If the meanderings interfere with your focus, therefore, just find ways of tolerating them. For instance, treat them as the musings of an elder-in-the-making, borrowing a leaf from the wazee wakumbuka (elders recollect), an extremely popular kipindi (program) that used to air on Kenya Broadcasting Corporation (KBC) radio network sometime in the 1970s.